2011
DOI: 10.1164/rccm.201105-0867oc
|View full text |Cite
|
Sign up to set email alerts
|

Attributable Mortality of Ventilator-Associated Pneumonia

Abstract: Our study on the attributable mortality of VAP is the first that simultaneously accounts for the time of acquiring VAP, informative loss to follow-up after ICU discharge, and the existence of complex feedback relations between VAP and the evolution of disease severity. In contrast to the majority of previous reports, we detected a relatively limited attributable ICU mortality of VAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
189
0
16

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 342 publications
(224 citation statements)
references
References 33 publications
12
189
0
16
Order By: Relevance
“…According to a large study including 1735 patients treated in 27 European ICUs, the rate of VAP in various age groups were 13.7, 16.6 and 13/1000 ventilators days in patients aged 45−64, 65−74 and older than 75 years, respectively [10]. The mortality among VAP patients is 70% or is controversially low (1-1.5%) when estimated after the error correction resulting from the impact of concomitant diseases [11,12]. A study performed in 88 689 individuals revealed that VAP caused statistically significant prolongation of mechanical ventilation (21.8 vs. 10.3 days, P < 0.0001), ICU therapy (20.5 vs. 11.6 days, P < 0.0001) and hospital treatment (32.6 vs. 19.5 days, P < 0.0001) [4].…”
mentioning
confidence: 99%
“…According to a large study including 1735 patients treated in 27 European ICUs, the rate of VAP in various age groups were 13.7, 16.6 and 13/1000 ventilators days in patients aged 45−64, 65−74 and older than 75 years, respectively [10]. The mortality among VAP patients is 70% or is controversially low (1-1.5%) when estimated after the error correction resulting from the impact of concomitant diseases [11,12]. A study performed in 88 689 individuals revealed that VAP caused statistically significant prolongation of mechanical ventilation (21.8 vs. 10.3 days, P < 0.0001), ICU therapy (20.5 vs. 11.6 days, P < 0.0001) and hospital treatment (32.6 vs. 19.5 days, P < 0.0001) [4].…”
mentioning
confidence: 99%
“…Estudos 27,28 demonstram que a incidência dessa infecção aumenta com a duração da ventilação mecânica e apontam taxas de ataque de aproximadamente 3% por dia durante os primeiros 5 dias de ventilação. O desenvolvimento de pneumonia nosocomial e no ambiente de cuidados intensivos, especificamente da PAV, tem morbidade significativa associada, prolongando o tempo de VM, bem como o tempo de permanência na UTI, com todos os custos associados a esse prolongamento 28,29 . Salienta-se que neste estudo, os pacientes foram acompanhados até a alta da UTI ou óbito.…”
Section: Discussionunclassified
“…The authors discuss the mortality issue pointing out that a survival analysis by Bekaert et al 4 only found an attributable mortality of 1% at 30 days due to VAP, which is likely to explain the review's result.…”
Section: Oral Healthmentioning
confidence: 97%